(untitled) (CIPEEX, 2022)
INTRODUCTION: SEPSIS IS A MAJOR HEALTH PROBLEM, SIMILAR TO ACUTE MYOCARDIAL INFARCTION (AMI), CEREBROVASCULAR ACCIDENT (STROKE) AND POLYTRAUMA. MORTALITY REACHES AN ALARMING NUMBER, AFFECTING 25% OF THE PATIENTS, IN ADDITION TO HIGH COSTS, SINCE THE PATIENTS AFFECTED NEED SOPHISTICATED EQUIPMENT AND CONTINUOUS ASSISTANCE OF A MULTIPROFESSIONAL TEAM. ITS EARLY RECOGNITION AND APPROPRIATE TREATMENT ARE KEY FACTORS IN CHANGING THIS SCENARIO. THEREFORE, THE IMPLEMENTATION OF PROTOCOLS IS AN IMPORTANT TOOL IN THIS CONTEXT, HELPING INSTITUTIONS TO STANDARDIZE SEPTIC PATIENT CARE, REDUCING NEGATIVE OUTCOMES AND PROVIDING BETTER TREATMENT EFFECTIVENESS (COREN-SP, 2016) (DELLINGER ET AL., 2016). OBJECTIVE: THIS STUDY AIMS TO EVALUATE THE USE OF THE SEPSIS PROTOCOL IN A HOSPITAL UNIT. METHODOLOGY: THIS WAS A CROSS-SECTIONAL, RETROSPECTIVE STUDY, A QUANTITATIVE DESCRIPTIVE DOCUMENTARY STUDY PERFORMED IN A MEDIUM-SIZED HOSPITAL WITH HIGH COMPLEXITY, IN THE INTERIOR OF GOIS. A TOTAL OF 441 SEPSIS PROTOCOLS WERE EVALUATED, WITH PROTOCOLS COMPLETED FROM OPENING TO CLOSING, FROM AUGUST / 2016 TO MAY / 2017. AND, MEDICAL RECORDS THAT DID NOT CONTAIN SEPSIS PROTOCOLS OR THAT WERE OUTSIDE THE ESTABLISHED PERIOD FOR DATA COLLECTION WERE EXCLUDED. RESULTS AND DISCUSSION: AMONG THE PATIENTS STUDIED, THE FEMALE GENDER PREVAILED (58%). AGE RANGED FROM 13 TO 109 YEARS. THE SECTOR WHERE THE OPENING TOOK PLACE STOOD OUT THE EMERGENCY ROOM (81%). THE NURSE WAS PRESENT IN 7.5%. THE MOST FREQUENT WARNING SIGN WAS HEART RATE> 90 BPM WHERE IT WAS PRESENTED BY 335 PATIENTS. THE MOST PREVALENT OUTBREAK WAS PNEUMONIA (42.8%). SEVERAL TOKENS WERE FOUND WITH IGNORED CHECKBOXES. THE NURSE IS THE PROFESSIONAL WITH GREAT RESPONSIBILITY FOR IDENTIFYING AND UNDERSTANDING THE CLINICAL MANIFESTATIONS CAUSED BY SEPSIS. THEREFORE, THE CARE PLAN IS EXTREMELY NECESSARY. FINAL CONSIDERATIONS: THE RESULTS OF THIS STUDY CONTRIBUTE TO IMPROVE THE PERCEPTION OF HEALTH PROFESSIONALS ABOUT THE SEPSIS PROTOCOL, AS IT REVEALS DATA PERTINENT TO THE EVALUATION OF THE USE OF THIS PROTOCOL IN A MEDIUM-SIZED HOSPITAL UNIT IN GOIS. IT WAS POSSIBLE TO EVIDENCE A LOW ADHERENCE IN THE CORRECT FILLING OF THE PROTOCOL, WHICH CAN BE IMPROVED WITH PERMANENT EDUCATION OF THE MULTIPROFESSIONAL TEAM. CONCOMITANTLY, THE PUBLICATION OF NEW STUDIES ABOUT THE SEPSIS PROTOCOL IS OF PARAMOUNT IMPORTANCE FOR THE ELUCIDATION OF ITS USE IN HOSPITAL UNITS, AS WELL AS ITS DISSEMINATION. CONSIDERING THAT THE PURPOSE OF THE SEPSIS PROTOCOL IS TO ASSIST THE INSTITUTIONS IN THE STANDARDIZATION OF SEPTIC PATIENT CARE, REDUCING NEGATIVE OUTCOMES AND PROVIDING BETTER TREATMENT EFFECTIVENESS. THE STUDY MADE IT POSSIBLE TO SHOW THAT WITH THE CORRECT USE OF THE PROTOCOL, NURSES CAN BASE THEIR DECISION MAKING ON THE PRODUCTION OF CARE. THEREFORE, THE CARE PLAN FOR THESE CHANGES IS EXTREMELY NECESSARY. THE RESULTS OF THE STUDY INDICATE THE NEED FOR SCIENTIFIC DEEPENING FOCUSING ON PATIENTS ADMITTED TO ICUS OF GENERAL HOSPITALS, PREFERABLY MULTICENTRIC AND WITH ORIENTATION OF TIMELY COLLECTION OF CULTURES IN THE FIRST HOUR OF SEPSIS TREATMENT. &NBSP;